The Effect of Work Supervision and Discipline on Employee Performance at PT. Personel Alih Daya (Persero) Jakarta Selatan - Muhammad Gandung (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study was to determine the effect of supervision and work discipline on employee performance at PT. South Jakarta Outsourcing Personnel (Persero). Either partially or simultaneously. The method used in this study is a quantitative method. The sampling technique used is saturated sampling using a sample of 80 respondents. The data analysis technique used is statistical analysis with validity test, rehabilitation test, classical assumption test, simple linear regression test, multiple regression test, correlation coefficient, coefficient of determination, hypothesis t test and hypothesis f test. The results of the supervision research have a significant effect on job satisfaction partially, as shown by the linear regression equation Y = 9.784 + 0.333 X1 where the coefficient value is positive, which means that if the work environment increases, job satisfaction will also increase. This is evidenced by testing the hypothesis that the value of t arithmetic > t table (11.677 > 1.664) is moderately related by the value < Sig 0.05 or significance < 0.05 (0.000 < 0.05). Work discipline has a significant effect on job satisfaction partially, as shown by the linear regression equation Y = 13.839 + 0.943 X2 where the coefficient value is positive, which means that if the work environment increases, job satisfaction will also increase. This is evidenced by the hypothesis test that the value of t count > t table (12,309 > 1,664) is moderately related by the value < Sig 0.05 or significance < 0.05 (0.000 < 0.05). The results of research on supervision and work discipline on employee performance are shown by the linear regression equation Y = 8.501 + 0.401 + -0.562 where the beta coefficient is positive, which means that if the work environment and motivation increase, job satisfaction will also increase. This is evidenced by the results of simultaneous hypothesis testing obtained by the calculated F value > F table or (93.996 > 3.12 ) and strengthened by a significance value < 0.05 (0.000 < 0.05). The results of the determination coefficient test of the supervisory variable (X1) and work discipline (X2) have an effect of 70.9% on the performance of employees at PT. Personel Alih Daya(Persero) Jakarta Selatan. Thus H0 is rejected and H3 is accepted. This means that it is proven that there is a simultaneous significant effect between supervision (X1) and work discipline (X2) on employee performance (Y).